Mental health effects on adolescent parents of young children: reflections on outcomes of an adolescent parenting programme in South Africa. Issue 1 (2nd January 2022) - Berry, Lizette; Mathews, Shanaaz; Reis, Ria; Crone, Mathilde
ABSTRACT: At-risk families and caregivers from low-and middle-income countries have been shown to benefit from parenting interventions. But there is limited evidence on the impact of interventions on adolescent parents. This paper considers the effects of a parenting programme targeting adolescent parents in South Africa, emphasising parenting and adolescent well-being outcomes. Secondly, it explores whether such an intervention can influence adolescent depression and parenting behaviours. Using a quasi-experimental, longitudinal design, data was collected over 2015–2017 from 113 adolescent parents (aged 12–22 years) who attended three secondary schools in Cape Town. Adolescents (biological and non-biological parents) were assigned to intervention (parenting programme participation) and control groups. They completed assessments on parenting, adolescent well-being, and social context at three time-points. Inter-group, and time-period differences were examined, and analyses on whether depression moderates programme effects on outcomes were conducted. At the ten-month follow-up, positive parenting and resilience improved for biological and non-biological parents and in both study groups. For the non-biological intervention group parents, depression rates increased over time. Intervention adolescents with high depression risk showed smaller improvements in supportive parenting than their control group counterparts. Although adolescents increased in positive parenting and resilience, it is unclear whether and how the intervention contributed to these results. As the intervention group included more adolescents at high risk of depression at follow-up, this study highlights the importance of including mental health support in interventions targeting adolescents in LMIC contexts. The study is limited by a small sample size and reliance on self-reported data.